Adequacy of traditional curette versus powered shaver for adenoid clearance: a comparative study - Kumaraswamy, Nagarathna Hosalli; Warhapande, Shruti S.; H. M., Saritha (International Journal of Contemporary Pediatrics, 2023)
Background: Adenoid growth is a prevalent aetiology of blockage of nasal passage in paediatric patients, and multiple techniques exist for their surgical removal. The objective of this investigation was to study the efficacy of the conventional curette versus the endoscopic guided powered shaver in the context of adenoid clearance. Methods: In this study, a comparative analysis was performed on a sample of 119 patients, consisting of two distinct groups. Group I-60 patients who underwent conventional adenoidectomy, while group II-59 patients who underwent endoscopic microdebrider-assisted adenoidectomy. The methods employed in this study were in accordance with established medical practises. The research evaluated outcome measures including surgical duration, haemorrhage, and perioperative and postoperative adverse events. Results: Group I, 17 (28.3%) received adenoidectomy as a standalone procedure, group II, 22 (37.3%) received adenoidectomy as a standalone procedure. An adenotonsillectomy was executed on 21 patients, accounting for 35% of group I, and 10 patients, accounting for 16.9% of group II. The study found that group I exhibited significantly reduced operation time and blood loss compared to group II (20.88±4.41 vs. 29.00±4.15 minutes and 13.47±3.02 vs. 18.64±3.16 millilitres, respectively). Intraoperative complications were observed in 10% of patients in group I and 5.1% of patients in group II. The group II participants exhibited a more rapid onset of symptomatic relief compared to those in group I. There was no evidence of recurrence in the cohort of patients who underwent endoscopic microdebrider-assisted adenoidectomy. Conclusions: Endoscopic microdebrider-assisted adenoidectomy is a superior and dependable technique compared to curettage, exhibiting improved clearance rates and patient contentment.